2018
DOI: 10.1080/09540105.2018.1457013
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofClostridium butyricumandLactobacillus plantarumon growth performance, immune function and volatile fatty acid level of caecal digesta in broilers

Abstract: The study was conducted to investigate the effects of Clostridium butyricum and Lactobacillus plantarum on growth performance, immune function and volatile fatty acid (VFA) level of caecal digesta in broilers. One hundred and forty broilers were assigned to five groups (CON: basal diet; CB: basal diet+ C. butyricum; MLP: basal diet+ L. plantarum; MIX: basal diet+ C. butyricum + L. plantarum; ANT: basal diet + Aureomycin). The results showed that, birds in CB group had greater serum IgM level than that in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 36 publications
4
32
1
Order By: Relevance
“…Association of Lb. plantarum (1 × 10 7 CFU/kg of feed) and Clostridium butyricum (1 × 10 6 CFU/kg of feed) on production performance and immune function in broilers revealed the increase of IgG and IgA levels in chickens fed with these beneficial probiotics (Han et al, 2018). In direct line, Lb.…”
Section: Pathogen Inhibitionmentioning
confidence: 99%
“…Association of Lb. plantarum (1 × 10 7 CFU/kg of feed) and Clostridium butyricum (1 × 10 6 CFU/kg of feed) on production performance and immune function in broilers revealed the increase of IgG and IgA levels in chickens fed with these beneficial probiotics (Han et al, 2018). In direct line, Lb.…”
Section: Pathogen Inhibitionmentioning
confidence: 99%
“…Beneficial effects of probiotics highly depend on species-and strain-specific, tolerance and adhesion in gastrointestinal tract (Corona-Hernandez et al, 2013). Lactic acid bacteria, such as Enterococcus faecalis, play an important role in intestinal tract by modulating gut microflora of animals (Han et al, 2018;Wang et al, 2018). However, lactic acid bacteria are very sensitive to the external environment, such as feed process, storage, and gastrointestinal tract of animal (Corona-Hernandez, Alvarez-Parrilla, Lizardi-Mendoza, Islas-Rubio, & de la Rosa, 2013;Prakash, Tomaro-Duchesneau, Saha, & Cantor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies showed that combined use of probiotics could promote growth performance in animals [ 35 , 36 , 37 , 38 ]. However, some research showed that combined use of probiotics exerted no significant effect on growth performance [ 39 ]. Our results found that compared with control, the effect of C. butyricum Sx-01, L. salivarius C-1-3, and their combined use on the growth performance of mice was not significant, but the average daily gain and feed utilisation showed an increasing trend.…”
Section: Discussionmentioning
confidence: 99%